2018
DOI: 10.14687/jhs.v14i4.4869
|View full text |Cite
|
Sign up to set email alerts
|

Sportsmanship tendency in terms of moral development of middle school students<p>Ortaokul öğrencilerinin ahlaki gelişimleri açısından sportmenlik yönelimleri

Abstract: This research aims to examine the sportsmanship orientations of secondary school students in terms of their moral developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
2
6
0
1
Order By: Relevance
“…In the study of Tel et al (2017) titled "Opinions of the Students in Faculty of Sports Sciences about the Sportspersonship Behaviors", it has been determined that females have higher sportspersonship scores than males. There are a lot of studies indicating that sportspersonship scores of females are higher (Tsai and Fung, 2005;Akandere et al, 2009;Gürpınar and Kurşun, 2013;Esentürk et al, 2015;Gümüş et al, 2016;Goksel and Zorba, 2017;Koç, 2017;Yilmaz et al, 2017). These findings are in parallel with the results of our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study of Tel et al (2017) titled "Opinions of the Students in Faculty of Sports Sciences about the Sportspersonship Behaviors", it has been determined that females have higher sportspersonship scores than males. There are a lot of studies indicating that sportspersonship scores of females are higher (Tsai and Fung, 2005;Akandere et al, 2009;Gürpınar and Kurşun, 2013;Esentürk et al, 2015;Gümüş et al, 2016;Goksel and Zorba, 2017;Koç, 2017;Yilmaz et al, 2017). These findings are in parallel with the results of our study.…”
Section: Discussionsupporting
confidence: 91%
“…There are also studies stating that sportsperson ship scores are higher in lower grades and lower in higher grades. In the study performed on secondary school students (Yilmaz et al, 2017) it has been determined that the higher the grade becomes, the lower the sportsperson ship behaviors of students are. Similar result is also observed in the studies of Yakup (2013) and Esentürk et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of sportsmanship expresses the fact that behaviours within sporting activity must conform to socio-ethical norms, that is, to the true spirit of sport (Yılmaz, Esentürk & İlhan, 2017). Displaying this type of behaviour becomes difficult particularly among those who perform this activity as professionals, when expectations are based on winning.…”
Section: Discussionmentioning
confidence: 99%
“…Both the training of athletes and the creation of awareness of the concept of sportsmanship while educating trainers can be achieved with the curricula planned by schools and sports clubs (Ford, Jubenville & Phillips, 2012). In the course of sports training, fundamental values such as the rivalry, equality of opportunity, cooperation, collaboration and tolerance that exist within the natural structure of lessons are considered as opportunities for individuals to acquire moral behaviours (Yılmaz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that in the case of establishing an ego-oriented atmosphere in coach-athlete relationships at the competition and training fields rather than a task-oriented atmosphere, there will be a high level of cheating and gamesmanship [13]. There are studies suggesting that individuals with an antisocial personality are more prone to such behavior as cheating and resorting to violence in the competition and that there is a direct relationship between moral conduct and proper behavior [3,14]. In a study conducted with young tennis athletes, it was observed that there was a relationship between the anti-social attitudes of the athletes and their cheating behaviors during the match, and there was a direct link between moral attitude and actual behavior [15].…”
Section: Introductionmentioning
confidence: 99%